2019
DOI: 10.1007/s10668-019-00384-7
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating for energy efficiency in Swedish shipping industry: interrelating practice and challenges

Abstract: As achieving environmental sustainability is a complex problem, it is often recognized that no organization can accomplish this systemic change by itself; thus, multi-actor collaboration is needed. Regarding the specific issue of increased energy efficiency, previous research has highlighted the need for collaboration and knowledge exchange among actors. However, insights from literature suggest that despite all the good intentions, establishing multi-actor collaboration can be both complicated and difficult t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Rather, the decisions just "happened" as a result of organizational priorities and practices. Borg and von Knorring (2019) and Borg and Yström (2019) conducted an ethnographic case study on a multi-actor collaboration project. The project aimed at knowledge sharing between companies for increased energy efficiency and included development of a database with energy efficiency measures, a series of workshops to educate onboard personnel in matters related to energy efficiency, and the establishment of a network of energy efficiency experts in the partner organizations.…”
Section: Cooperation Communication and Knowledge Sharing Between Stak...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the decisions just "happened" as a result of organizational priorities and practices. Borg and von Knorring (2019) and Borg and Yström (2019) conducted an ethnographic case study on a multi-actor collaboration project. The project aimed at knowledge sharing between companies for increased energy efficiency and included development of a database with energy efficiency measures, a series of workshops to educate onboard personnel in matters related to energy efficiency, and the establishment of a network of energy efficiency experts in the partner organizations.…”
Section: Cooperation Communication and Knowledge Sharing Between Stak...mentioning
confidence: 99%
“…Few participants engaged in the workshops and expert networks because of difficulties of engaging people to participate and managing conflicting opinions about collaboration structures and goals as well as problems in concretizing and agreeing on shared visions. Borg and von Knorring (2019) and Borg and Yström (2019) showed that the failure to create the energy efficiency database and expert-network project had mainly to do with the inability of the stakeholders to agree on a mutual agenda and shared goals.…”
Section: Cooperation Communication and Knowledge Sharing Between Stak...mentioning
confidence: 99%